(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
Bendung Tegalin Kapanewon Imogiri, Bantul Regency, Yogyakarta is one of the dams built to stem the flow of the Opak River to irrigate the surrounding rice fields. Besides functioning as irrigation, this dam was also developed as a tourist area by the local government. The development of Bendung Tegal Tourism is absolutely necessary because this can encourage the improvement of the economic conditions of the residents around it. Community participation is carried out in the development of the Tegal Weir tourism object by making monthly contributions for the people in the Kebonagung Tourism Village itself in the form of providing voluntary funds. Where the funds were obtained from the local community and youth youth organizations who participated in the management and development of the Tegal Dam tourist attraction. In addition, it is also necessary to improve both facilities and infrastructure to increase the level of tourist visits to the Bendung Tegal and in addition to the need for effective promotional media so that the Bendung Tegal Tourism Object is increasingly known by thepublic.